PEMIKIRAN K.H. MAIMUN ZUBAIR TENTANG METODE PENETAPAN AWAL BULAN RAMADHAN DAN SYAWAL DALAM KITAB NUSUS AL-AKHYAR DAN RISALAH FI MAUQIFINA HAULA AS-SAUM WA AL-IFTAR - Hibaurrohman, Imam Labib (Economics, Social, and Humanities Journal (Esochum), 2024)
K.H. Maimun Zubair or often known as Mbah Mun is known not only as a community leader and cleric but is highly respected by scholars at the national and international levels. He is a writer who has a variety of works. Some of his book are Nusus al-Akhyar and Risalah Fi Mauqifina Haula as-Saum Wa al-Iftar. This article examines Mbah Mun's method in determining the beginning of Ramadan and Shawwal as written in the books Nusus al-Akhyar and Risalah Fi Mauqifina Haula as-Saum Wa al-Iftar. This research is a qualitative research with primary data sourced from the book Nusus al-Akhyar and Risalah Fi Mauqifina Haula as-Saum Wa al-Iftar, the results of interviews, as well as various documents related to the focus of research. The data were analysed to answer the research problem. The results showed that in both books Mbah Mun explains how the method of determining the beginning of Ramadan and Shawwal is not only using astronomical calculations but must also be proven by rukyah bil fi'li. For him, rukyah bil fi'li is more certain than using calculations. While in his calculations, he tends to use the calculation of the Aboge Islamic Javanese Calendar as a basis for determining approximately when the beginning of the month of Ramadan or Shawwal occurs. Mbah Mun revealed that in rukyah bil fi'li it must be based on calculations but in its determination, it must wait for the results of rukyah. If it is not seen then the existing month must be completed to 30 days. Secondly, this study shows that in determining the beginning of the months of Ramadan and Shawwal, Muslims must follow the government's decision, which in this case is represented by the Ministry of Religious Affairs by considering the overall benefit so that there is no confusion between people.